2008
DOI: 10.1097/mph.0b013e3181639afe
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Aberrant Pre-mRNA Splicing by Antisense Oligonucleotides in β-Thalassemia Egyptian Patients With IVSI-110 Mutation

Abstract: The splicing mutation in intron 1 of beta-globin gene (IVS1-110) is the most common mutation in Egyptian thalassemics that causes aberrant splicing of pre-mRNA and deficient beta-globin chain synthesis. Antisense oligonucleotides (ASONs) are compounds that redirect pre-mRNA splicing and modify gene expression. Our aim was ex vivo correction of the aberrant splicing of beta-globin110 pre-mRNA by ASON against the 3' aberrant splice site. Peripheral blood mononuclear cells of 10 thalassemic patients with IVS1-110… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Blocking cryptic 5′ss with ASOs has been used in several disease models to correct splicing (Table 1, cryptic splice sites ) . ASO‐directed blocking of cryptic splice sites caused by mutations in HBB (β ‐globin), FKTN, LMNA , and CLC1 has been shown to rescue normal splicing in mouse models of β ‐thalassemia,39–43 Fukuyama congenital muscular dystrophy,50 Hutchinson‐Gilford progeria,53 and myotonic dystrophy,60 respectively (Table 1, cryptic splice sites). Also, rescue of disease phenotype in a mouse model has been shown using ASOs targeting a mutation the USH1C gene that creates a cryptic 5′ss and causes Usher syndrome.…”
Section: Targeting Splicing In Disease: the Fixesmentioning
confidence: 99%
“…Blocking cryptic 5′ss with ASOs has been used in several disease models to correct splicing (Table 1, cryptic splice sites ) . ASO‐directed blocking of cryptic splice sites caused by mutations in HBB (β ‐globin), FKTN, LMNA , and CLC1 has been shown to rescue normal splicing in mouse models of β ‐thalassemia,39–43 Fukuyama congenital muscular dystrophy,50 Hutchinson‐Gilford progeria,53 and myotonic dystrophy,60 respectively (Table 1, cryptic splice sites). Also, rescue of disease phenotype in a mouse model has been shown using ASOs targeting a mutation the USH1C gene that creates a cryptic 5′ss and causes Usher syndrome.…”
Section: Targeting Splicing In Disease: the Fixesmentioning
confidence: 99%
“…In this respect, ex vivo experiments based on the correction of splicing defects causing β -thalassemia have been reported by several research groups using antisense phosphorothioate 2′-O-methyl-oligonucleotides [ 45 , 46 ], morpholino-oligonucleotides [ 18 , 47 ], 2′-O-(2-methoxy) ethyl-oligonucleotides [ 47 ], and peptide nucleic acids [ 48 ]. These antisense molecules have been used either free [ 45 , 46 ] or delivered with peptides and lipid-based strategies [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…These antisense molecules have been used either free [ 45 , 46 ] or delivered with peptides and lipid-based strategies [ 49 ]. For instance, El-Beshlawy et al [ 18 ] reported the ex vivo correction of the aberrant splicing of IVSI-110 β -globin pre-mRNA by antisense oligonucleotides (ASONs) against the 3′ aberrant splicing site. In their study, ErPCs with the IVSI-110 mutation were treated with 20 μ mol/mL morpholino ASONs targeting the 3′ aberrant splicing site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SSOs modulate RNA splicing by redirecting alternative splicing that can be categorized in four mechanisms: exon skipping, exon retention, restoration of correct splicing and displacement of splicing factors from triplets repeats which have been reviewed extensively. 28 The SSOs have been used to correct aberrant splicing in β-thalassemia alleles including the mutations IVS1-110, 34 , 35 IVS2-654, 36 38 IVS2-705, 39 IVS2-745, 40 and βE. 36 SSOs successfully induced correct splicing and increased normal β-globin production in cell-free extracts, stable cell lines with a mutated β-globin gene, erythroid mononuclear cells from peripheral blood of patients, thalassemic mouse erythroid progenitors, human iPSCs and β-thalassemic mouse model.…”
Section: Nucleic Acid Therapy For β-Thalassemiamentioning
confidence: 99%